Significant enhancement in stability of copper nanowires network deposited by alumina via atomic layer deposition for transparent electromagnetic interference shielding - Cheng, Kuifu; Liang, Xianwen; Zhao, Tao; Liu, Dan; Lai, Zhiqiang; Fu, Xianzhu; Sun, Rong (2022 23rd International Conference on Electronic Packaging Technology (ICEPT), 2022)
Copper nanowires (CuNWs) have attracted ever-increasing attention in flexible electronic applications due to their excellent electrical conductivity, optical transparency, mechanical flexibility and low cost, as a consequence of which CuNWs transparent conductive films are even considered as a promising alternative to indium tin oxide (ITO) for optoelectronic devices. However, CuNWs are subject to oxidation, severely limiting their widespread applications in electronic devices, which is still an issue to be addressed urgently. In this study, as-prepared copper nanowires network is treated with citric acid and plasma to remove oxide and surficial organic capping agent, respectively, and then deposited by alumina (Al 2 O 3 ) via atomic layer deposition (ALD). The dense Al 2 O 3 shell can effectively protect CuNWs from oxygen and moisture in the air. Sheet resistance of the Al 2 O 3 deposited CuNWs (Al 2 O 3 @CuNWs) network only rises slightly in the test of 85 °C and 85% relative humidity for 15 days, while sheet resistance of pristine CuNWs network increases beyond multimeter limit only in 80 min. Optical property of the CuNWs network shows a little change after deposition of Al 2 O 3 . And the Al 2 O 3 @CuNWs network displays excellent flexibility, especially, which is far superior to ITO. Also, electromagnetic interference (EMI) shielding effectiveness (SE) of the Al 2 O 3 @CuNWs network exhibits outstanding stability after 85 °C and 85% relative humidity test, underscoring a significant promise in the applications of displays, touch panels, airborne optoelectronic pods and aviation camcorders.